AVOIDING POPLITEAL NEURO-VASCULAR INJURY DURING ILIOTIBIAL BAND ACL RECONSTRUCTION. Issue 7 (30th July 2021) - Shea, Kevin G; Tompkins, Marc; Vuong, Brian; VandenBerg, Curtis; Shea, Cooper; Wilson, Phil; Green, Dan; Ganley, Ted; Ellis, Henry
Background: For patients with significant growth remaining, the Iliotibial Band ACL reconstruction technique has proven to be reliable procedure with minimal risk for growth disturbance. Recent dissection studies confirm the neuro-vascular bundle is within 1 cm of the ACL graft over the top position, confirming the importance of careful graft passage technique to avoid neurovascular injury. Purpose: The purpose of this study was to evaluate the over the top graft passage technique using pediatric 3-D knee models. Instrument placement for graft passage was assessed for its proximity to the posterior aspect of the femur, maintaining a safe distance from the neurovascular bundle. Materials and Methods: 3D knee models (ages 7, 9, 11 years) were printed from high resolution knee CT scans, including a hinge/pivot mechanism to allow for simulation of knee position during flexion and extension. Various curved tip instruments were used to evaluate the path of the graft passage, with several goals: 1. Allow the instrument to create a graft path through the posterior capsule in the most anatomic femoral position. 2. Keep the tip of the instrument close to posterior and lateral cortex of the femur, to avoid neurovascular injury. The instruments varied in design, arc of curvature, overall length, diameters. Results: Clamp passage was performed using a retrograde approach, i.e. through the notch, passing outside the periosteum of the postero-lateral femur (Figure 1). For some clamps, the arc of the curvature allowed for passage of the instrument with minimal risk of neurovascular injury. For some clamp configurations, the clamps deviated significant from the posterior aspect of the femur during graft passage, which may increase the risk of neurovascular bundle injury. In each case, an instrument was identified that met the criteria for safe passage, but different instruments were required based upon the size of the knee joint. Conclusions: The ITB ACL reconstruction is one of the best options for ACL reconstruction in the skeletally immature. The neurovascular structures are very close to the path for over the top graft placement. Due to the wide range of knee dimensions in this group, different clamp designs may be necessary for optimal over the top graft passage. 3D knee models may guide surgeons for procedure technique and optimal instrument selection for safe graft passage. : Figure 1.